Ascertaining the influence of grid vs. non-grid techniques on radiation dose to the skull, eyes, and thyroids and image quality in anteroposterior (AP) skull X-ray examinations: a phantom study - Sayed, Inayatullah Shah; Abdullah, Fatin Amirah (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: Skull radiography plays a pivotal role in diagnosing traumatic head injuries, yet concerns persist regarding radiation exposure to organs, such as the brain, eyes, and thyroids. This study addresses the often-overlooked radiation protection measures for these organs, particularly in anteroposterior (AP) skull radiography cases. The utilization of a grid is essential for visualizing intricate cranial details, encompassing both soft tissues and bony structures. However, grid usage typically necessitates higher exposure settings compared to the non-grid technique. Thus, we investigate the effects of grid and non-grid techniques on entrance surface dose (ESD) to the brain, and radiation dose to the eyes and thyroid, and image quality. Methods: The Kyoto Kagaku Anthropomorphic PBU-50 head phantom was exposed with the Siemens Multix Top X-ray system. Various exposure parameters were explored, including (68 kVp, 9 mAs), (68 kVp, 12.5 mAs), (75 kVp, 9 mAs), and (75 kVp, 12.5 mAs). ESD for skull, eyes, and thyroid were measured using optically stimulated luminescence dosimeters (OSLDs) positioned at the glabella, eyes, and thyroid on the phantom. Image quality was assessed using the Image Criteria Score (ICS). Results: The analysis revealed that there was no significant difference in ESD between the grid and non-grid techniques when considering the larger OID (p > 0.05). However, a significant distinction in image quality emerged between the two techniques, especially for lower exposure factor (p < 0.05). Remarkably, the non-grid technique with a 4 cm air gap (OID) exhibited slightly higher ESD values in comparison to the grid technique (no air gap) when employing identical exposure parameters. Conclusion: Using the grid technique with no air-gap led to lower ESD values and better image quality, even at the lowest exposure settings. Additionally, this study found that the radiation dose values for the eyes and thyroid remained remarkably low for images attaining the highest ICS scores. These findings underscore the importance of optimizing radiographic techniques to achieve a balance between image quality and radiation dose for brain, eyes and thyroids in AP skull radiography.